Progress on sodium reduction in South Korea. Issue 5 (12th May 2020) - Park, Hye-Kyung; Lee, Yoonna; Kang, Baeg-Won; Kwon, Kwang-il; Kim, Jong-Wook; Kwon, Oh-Sang; Cobb, Laura K; Campbell, Norman R C; Blakeman, Drew E; Kim, Cho-il
Abstract : Introduction: High dietary sodium is a leading contributor to hypertension, and hypertension is the leading underlying cause of death globally. There is a robust body of evidence supporting the health benefits of sodium reduction. Sodium intake in South Korea is high, with about half the population consuming > 4000 mg/day, twice the recommended upper limit. Methods: In 2012, South Korea implemented its National Plan to Reduce Sodium Intake, with a goal of reducing population sodium consumption by 20%, to 3900 mg/day, by 2020. The plan included five key components: (1) a consumer awareness campaign designed to change food consumption behaviours; (2) increased availability of low-sodium foods at schools and worksites; (3) increased availability of low-sodium meals in restaurants; (4) voluntary reformulation of processed foods to lower sodium content; and (5) development of low-sodium recipes for food prepared at home. Monitoring and evaluation included tracking sodium intake and sources of dietary sodium using the Korea National Health and Nutrition Examination Survey. Results: By 2014, South Korea had reduced dietary sodium consumption among adults by 23.7% compared to a survey conducted in 2010 prior to implementation of a nationwide salt reduction campaign that used this comprehensive, multipronged approach. The reductions in sodium intake were accompanied by reductions in population blood pressure and hypertension prevalence. Although causal associations between the sodium reduction programme and reduced sodium intake cannot be made, the declines occurred with the introduction of the programme. Conclusion: Multicomponent interventions have great potential to reduce population sodium intake. Lessons learnt from South Korea could be applied to other countries and are likely very relevant to other Asian countries with similar food sources and consumption profiles.